9. PERKEMBANGAN KEPENDUDUKAN KUALITAS PENDUDUK DAN KETAHANAN PANGAN - Rodhiyah, Rodhiyah (Faculty of Social and Political Sciences Diponegoro University, 2008)
This study attempts contribute on the understanding of regional polulation dynamics in Indonesia. It outlines a detailed analysis of the changes in regional demographic variables during the last three decades. It provides an assessment of the past polupation projections, as well as the advantages offered by available demographic data sources. The resulting multiregional projections give an idea of a likely polulation that Indonesia and its regions will have up to the year 2-2- if the regional dimension is taken into account in the demographic scenarios applied.